Institutional delivery in public and private sectors in South Asia: a comparative analysis of prospective data from four demographic surveillance sites. Issue 1 (December 2016) - Das, Sushmita; Alcock, Glyn; Azad, Kishwar; Kuddus, Abdul; Manandhar, Dharma; Shrestha, Bhim; Nair, Nirmala; Rath, Shibanand; More, Neena; Saville, Naomi; Houweling, Tanja; Osrin, David
Abstract Background Maternity care in South Asia is available in both public and private sectors. Using data from demographic surveillance sites in Bangladesh, Nepal and rural and urban India, we aimed to compare institutional delivery rates and public-private share. Methods We used records of maternity care collected in socio-economically disadvantaged communities between 2005 and 2011. Institutional delivery was summarized by four potential determinants: household asset index, maternal schooling, maternal age, and parity. We developed logistic regression models for private sector institutional delivery with these as independent covariates. Results The data described 52 750 deliveries. Institutional delivery proportion varied and there were differences in public-private split. In Bangladesh and urban India, the proportion of deliveries in the private sector increased with wealth, maternal education, and age. The opposite was observed in rural India and Nepal. Conclusions The proportion of institutional delivery increased with economic status and education. The choice of sector is more complex and provision and perceived quality of public sector services is likely to play a role. Choices for safe maternity are influenced by accessibility, quantity and perceived quality of care. Along with data linkage between private and public sectors, increased regulation should be part of the development of the pluralistic healthcare systems that characterize south Asia.